When Machine and Human Meet. Art in the Age of Artificial Intelligence - Sylwia Szykowna (Acta Universitatis Lodziensis: Folia Philosophica, 2025)
This article touches on the issue of human-technology relations in the age of artificial intelligence. It poses questions about the changes that have taken place in the field of art under the influence of advanced machine learning systems. The last decade of AI’s successes enforces the need to rethink the aesthetic categories, including an attempt to redefine the place and role of the artist in a technologically determined reality. The cited historical examples of aesthetic reflection accompanying computer art of the 1960s largely anticipated the changes taking place today, while also serving an important metacritical function. Today’s critical AI art can play a key role in raising awareness of the processes taking place and uncovering the workings of artificial intelligence algorithms, which are often locked in black boxes and their operations and assumptions inaccessible to human understanding.